PENGARUH VARIASI ARUS LISTRIK TERHADAP KEKUATAN TARIK GESER LAS TITIK BEDA MATERIAL STAINLESS STEEL DAN ALUMINIUM - Ahmadil Amin; Syarifil Anwar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The use of electric current will be related to heat input. Enough heat input is needed to form a good nugget structure so that it can produce maximum connection strength. The nugget structure is influenced by electrode pressure, holding time and the electric current used. By adjusting the parameters of the amount of electric current, the best connection quality will be produced. The purpose of this study is to determine the effect of variations in electric current on the shear tensile strength of dissimilar welding Stainless steel (SS) and Aluminum (Al). The variation of electric current used is 60 A, 70 A and 80 A. The welding time used is 4 seconds. The test material uses stainless steel material with a thickness of 1.2 mm and aluminum with a thickness of 0.9 mm. This research was conducted at the Kotabaru Polytechnic Mechanical Laboratory and Malang State Polytechnic Material Test Laboratory. Tests carried out are shear tensile tests according to ASME (American Society of Mechanical Engineering) standards. The results showed that an increase in electric current from 60 A to 70 A had an impact on the increase in shear tensile strength. While the increase in electric current from 70 A to 80 A shows a decrease in shear tensile strength. The results of shear tensile testing indicate that the best conditions occur at 70 A electric current which gives a shear tensile strength of 44.109 kN / mm2. The increase in the electric current at the dissimilar welding between Stainless Steel and Aluminum is not directly proportional to the increase in shear stress that occurs. This is because the melting point of each material is different. If the heat generated exceeds the melting point of the material used, the welding results will be damaged.